Existence of Marriage Agreements in Islam Development Studies in the Community of Malay Border Indonesia-Malaysia - Asman Asman; Marilang Marilang; Kurniati Kurniati (IAIN Manado, 2021)
This article explains how the Existence of the Marriage Agreement in the Sambas Community of the Indonesia-Malaysia Border. Based on the pros and cons of the Sambas Malay Society, especially about the marriage agreement regarding taklik talak as a marriage agreement in Islam. With qualitative research methods that are phenomenological observations in the field, the author wants to describe how the existence of divorce taklik talak as a marriage agreement in Islam itself and its practice in the Sambas Malay Community and the reasons for the pros and cons of religious leaders. Almost every prospective husband and wife in marriage to the Sambas Malay Community does not say sighat taklik talak by the husband to his wife after the ijab qobul consent. Sighat taklik talak only knowing that it has been written or listed in a marriage book without being notified to the husband and wife. Although divorce taklik talak has written in the marriage certificate is not an obligation to say. Still, once taklik talak has said, the taklik talak cannot be revoked again. If an agreement with a husband and wife did not fulfil by one of the parties, then the other party has the right to submit the matter to the Religious Court to resolve it. The study concludes that the pros and cons of divorce taklik talak as a marriage agreement in Islam cause a lack of knowledge about Marriage Law Number 1 of 1974 article 29 regarding marriage agreements and the Compilation of Islamic Law (KHI) Article 46 concerning taklik talak. And the lack of socialization of related parties from KUA through religious counsellors and BP4 in Sambas.